2022
DOI: 10.1186/s40001-022-00816-7
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a prediction model for recurrence of condyloma acuminatum

Abstract: We collected the clinical data of 156 patients diagnosed with condyloma acuminatum (CA), including age, gender, marriage, education level, stay up late, smoking, drinking, number of sexual partners, HPV infection status of sexual partners, genitourinary and anal diseases, condom use, other diseases of HPV infection, location and number of warts, HPV typing, etc. Analyze the risk factors affecting the recurrence of CA, explore the influencing factors and independent influencing factors of CA recurrence, establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 31 publications
0
9
2
Order By: Relevance
“…Relapses often occur 3 months after treatment. [6,8] In this case, there was no recurrence after a 3-month followup.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Relapses often occur 3 months after treatment. [6,8] In this case, there was no recurrence after a 3-month followup.…”
Section: Discussionmentioning
confidence: 57%
“…A study in China found that 59.6% of cases were in males, 32% were over 50 years old, and 48.7% were married. [8] In this case, the patient is a 53-year-old married male. Transmission of condyloma acuminata occurs through sexual contact, direct contact with HPV-contaminated objects, and from an infected mother to a child during childbirth.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…This may lead to ineffective T cell activation leading to a lack of immunological ignorance and/or tolerance of virus-infected cells. 41 Another study reported that patients with genitourinary infections are prone to AGW recurrence due to repeated stimulation of the skin and mucosa by various pathogens resulting in an increase of HPV colonization. The number of skin lesions are an independent influencing factor for AGW recurrence which causes declinine in the immune system to inhibit and eradicate HPV by T lymphocyte cells.…”
Section: Discussionmentioning
confidence: 99%
“…There are also cases of auto-inoculation and vertical transmission. 90% of CA is caused by 2 low-risk subtypes, 6 and 11 ( 2 ), while some are also associated with other subtypes, such as 16, 18, 31, 33, and 35. Due to the moist environment of the genital area and excessive folds in the cavity, viruses have an easy chance to hide with a low spontaneous clearance by the body; warts are widely spread, which have a high recurrence rate.…”
Section: Introductionmentioning
confidence: 99%